2012
DOI: 10.1163/18739865-00503011
|View full text |Cite
|
Sign up to set email alerts
|

Media and Democracy in Turkey: Toward a Model of Neoliberal Media Autocracy

Abstract: This paper reveals the ways in which media autocracy operates on political, judicial, economic and discursive levels in post-2007 Turkish media. Newsmakers in Turkey currently experience five different systemic kinds of neoliberal government pressures to keep their voice down: conglomerate pressure, judicial suppression, online banishment, surveillance defamation and accreditation discrimination. The progression of restrictions on media freedom has increased in volume annually since 2007; this includes pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 17 publications
(9 reference statements)
0
37
0
Order By: Relevance
“…In the same spirit, Aksera and Baybars‐Hawksb (, p. 302) argue that, “Turkish media is under siege today by the ruling government of the AKP,” and that “The level of political pressure and legal restraints on news‐reporting are visible in an unprecedented scale.” According to Yildiz (), there are “four types of newspapers in Turkey; pro‐Gülen, opposition, pro‐Erdoğan and swing.” Sabah newspaper and, therefore, http://www.dailysabah.com is categorized under the pro‐Erdoğan newspapers as it was recently “taken over by a group of companies who are all close” to him (Akoz, ; Aydıntaşbaş, ; Yildiz, ). Moreover, the brother of the CEO of the owning company (Turkuvaz Media Group – Çalık Holding), is the son‐in‐law of president Erdoğan (Corke, Finkel, Kramer, Robbins, & Schenkkan, , p. 7).…”
mentioning
confidence: 99%
“…In the same spirit, Aksera and Baybars‐Hawksb (, p. 302) argue that, “Turkish media is under siege today by the ruling government of the AKP,” and that “The level of political pressure and legal restraints on news‐reporting are visible in an unprecedented scale.” According to Yildiz (), there are “four types of newspapers in Turkey; pro‐Gülen, opposition, pro‐Erdoğan and swing.” Sabah newspaper and, therefore, http://www.dailysabah.com is categorized under the pro‐Erdoğan newspapers as it was recently “taken over by a group of companies who are all close” to him (Akoz, ; Aydıntaşbaş, ; Yildiz, ). Moreover, the brother of the CEO of the owning company (Turkuvaz Media Group – Çalık Holding), is the son‐in‐law of president Erdoğan (Corke, Finkel, Kramer, Robbins, & Schenkkan, , p. 7).…”
mentioning
confidence: 99%
“…This specific case told all other media conglomerates and media bosses that the government can impose fines over taxes on media groups when they become critical of the government and topple media conglomerates. It is not claimed here that the economic measures that are taken against media conglomerates by the government are illegal; however, it is interesting that they are enforced when these companies become critical of the government (Akser & Baybars-Hawks, 2012;pp 307-308). Doğan group, which controlled almost half of all the print, audio-visual and new media in Turkey went through a similar crisis after they covered a court case that took place in Germany on the misuse of donations to Lighthouse Foundation, an NGO in Germany, and questioned the governments' involvement in the fraud.…”
Section: Resultsmentioning
confidence: 99%
“…Doğan group, which controlled almost half of all the print, audio-visual and new media in Turkey went through a similar crisis after they covered a court case that took place in Germany on the misuse of donations to Lighthouse Foundation, an NGO in Germany, and questioned the governments' involvement in the fraud. Erdoğan accused the media group of fraud and with being biased and invited the public to boycott Doğan Media (Akser & Baybars-Hawks, 2012; pp 307-308). Although it was interesting to see that Doğan Media Group, which has always advocated the governments' practices, became critical only after they could not get the approval for a refinery in Ceyhan (a coastal town at the crossroads of a petroleum pipelines) from the government, the consequences of this dispute taught the media and the public once again that the government had the power to cause changes in the media (Kaya &Çakmur, 2010, p. 532).…”
Section: Resultsmentioning
confidence: 99%
“…They have argued that the Internet and social media have become crucial spaces for dissenting voices sidelined by other outlets (Çelik, ; C. Christiansen, ; Tufekci, ; Tunç, ). And they have revealed that aggressive state regulation and Internet censorship have catalyzed a vibrant circumvention culture in Turkey (Harris, ) where virtual private network (VPN) tunneling, anonymity, and self‐censorship are common (Akser & Baybars‐Hawks, ; Baybars‐Hawks, ).…”
mentioning
confidence: 99%